Different Surgical Approaches for treatment of isolated dissociated vertical deviation without inferior oblique overaction. Issue 6 (November 2022) - Fu, Licheng; Zhu, Binbin; Yang, Dingping; Yan, Jianhua
Purpose: To report the surgical results on superior rectus recession (SRR) and inferior oblique anterior transposition (IOAT) for cases with isolated bilateral dissociated vertical deviation（DVD）without inferior oblique overaction (IOOA). Methods: A retrospective review was conducted for cases with isolated bilateral DVD without IOOA who were surgically treated using either bilateral SRR (SRR group) or IOAT (IOAT group). Pre- and post-operative ocular motility, ocular alignment, amount of DVD and complications were compared between the two groups. Results: Records from 37 cases were reviewed. Preoperative levels of DVD (M ± SD) in the SRR group (N = 18) of 19.88 ± 6.72 prism diopter (PD) in the right eye and 19.54 ± 5.64 PD in the left eye, were reduced to 4.94 ± 7.26 PD and 4.11 ± 3.91 PD respectively after surgery (P＜0.0001 for both). Preoperative levels of DVD (M ± SD) in IOAT group (N = 19) of 15.89 ± 6.35 PD in the right eye and 18.58 ± 9.27 PD in the left eye, were reduced to 3.42 ± 4.49 PD and 3.42 ± 4.88 PD respectively after surgery (P＜0.0001 for both). Inferior oblique (IO) muscle function remained normal after surgery. Overall, outcomes within the SRR group revealed that 10 patients showed a complete resolution of their condition, 6 effective responses and 2 failures. In the IOAT group, 13 patients showed a complete resolution of their condition, 5 effective responses and 1 failure. There were no statistically significant differences between the two groups (Z = 0.48). Conclusion: SRR and IOAT were both effective in treating isolated DVD without IOOA with similar satisfactory results obtained for both procedures.